Business Feasibility Research in Opening Learning Centre at Balaraja based on SWOT and AHP Method - Yunita, Yunita (Swiss German University, 2019)
Business feasibility research is needed before business development team decided to start the business. SWOT analysis is an important part of it, since it described Strength – Weaknesses – Opportunity – Threats. However the result have no score, so its makes harder to consider each part in making decision. AHP (Analytic Hierarchy Process) is one of the method in decision tool to scoring, AHP carry the quantitative analysis of the problem. The combine of SWOT and AHP in feasibility research provide more reliable accurate in decision making. The aim of this paper is to analyze the business feasibility in opening learning centre at Balaraja based on SWOT and AHP method.